Speaking Anxiety Experienced by Eleventh Grade Students at SMA N 2 Pariaman : Level and Coping Strategies. - Rezki Hermansyah; Delvi Wahyuni (Journal of English Language Teaching, 2021)
This research is descriptive quantitave research. The purpose of this research istofind out the level of students speaking anxiety and coping strategy used by the students in dealing with speaking anxiety. The population of this research was the second year students at SMA N 2 Pariaman. The research sample was 70 students of class XI IPA. The instrument of this research was a questionnaire, foreign language speaking anxiety questionnaire (FLSA) it was adopted from  Öztürk & Gürbüz (2014) and coping strategy questionnaire it was adopted from Kondo & Yang (2004).The results of this study is first, most of the students experienced the moderate level of speaking anxiety. Second, there are five strategies used by the students to cope with speaking anxiety they are preparation, relaxation, positive thinking, peer-seeking, and resignation. Dominant coping strategies used by the students is positive thinking and less dominant strategy used by the students is resignation.